The Relationship between Exploring New Meanings of Caregiving and Family's Ability to Care Schizophrenia - Nia Agustiningsih; Dwi Indah Iswanti; Fery Agusman Motuho Mendrofa (Universitas STRADA Indonesia, 2025)
Background: Families who care for patients with schizophrenia are still considered negative experiences. Families are less able to find new, positive meaning when caring for patients with schizophrenia. This condition increases the family's and patient's burden as well as the inability of families to care for patients with schizophrenia. Purpose: This research aims to identify relationships between exploring the new meaning of caregiving with the family's ability to take care of patients with schizophrenia. Methods: This research is a quantitative descriptive study with a cross-sectional approach. A sample of 135 families who were caregivers of patients with schizophrenia was selected using purposive sampling techniques. The questionnaire exploring the new meaning of caregiving was developed from the concept of integrative empowerment and the family's ability to care for schizophrenia from the Barthel Index questionnaire and the Caregiving Tasks in Caring for an Adult with Mental Illness Scale (CTiCAMIS). Data analysis used Spearman rank correlation with alpha 5%. Results: This study's result is that the family's ability to explore new meanings of care is still in the sufficient category, both in the family aspect of having responsibility, the ability to assess positive aspects, acceptance of caring situations, and the family being part of the healer. Meanwhile, families' ability to care for patients with schizophrenia is still lacking to help with social interaction and productive skills. Conclusion: There is a relatively strong and unidirectional relationship between exploring new meanings of caregiving and the family's ability to care for schizophrenia (p-value=0.000; rho=0.311). Nurses must train family skills to explore new meanings through family empowerment programs.